2020
DOI: 10.1002/ijop.12718
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic stress symptoms and post‐traumatic growth in children and adolescents 12 months and 24 months after the earthquake and tsunamis in Chile in 2010: A longitudinal study

Abstract: On 27 February 2010, Chile experienced one of the strongest earthquakes in recorded history. The study aimed to evaluate post‐traumatic stress symptoms (PTSS) and post‐traumatic growth (PTG) in children and adolescents 12 months (T1) and 24 months (T2) after the earthquake and tsunamis in Chile in 2010. Three hundred twenty‐five children and adolescents (47.4% girls; 52.6% boys) between the ages of 10 and 16 years participated in the study. The instruments included the Revised Post‐traumatic Growth Inventory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Not only is it frightening, but stress can also result from the destructions that it leaves afterward including house damages, loss of possessions, forced migration, and disruptions to social networks, environments, and local economy. Losing a beloved relative to a disaster can cause an incredibly deep sadness and adolescents might find it more difficult to process such losses (Andrades et al, 2021;Kousky, 2016). Furthermore, children and adolescents are particularly at risk of developing post-traumatic stress symptoms after experiencing a natural disaster (Andrades et al, 2021;Brown et al, 2017;Kousky, 2016;Rezwana et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Not only is it frightening, but stress can also result from the destructions that it leaves afterward including house damages, loss of possessions, forced migration, and disruptions to social networks, environments, and local economy. Losing a beloved relative to a disaster can cause an incredibly deep sadness and adolescents might find it more difficult to process such losses (Andrades et al, 2021;Kousky, 2016). Furthermore, children and adolescents are particularly at risk of developing post-traumatic stress symptoms after experiencing a natural disaster (Andrades et al, 2021;Brown et al, 2017;Kousky, 2016;Rezwana et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Natural disasters may affect individuals differently (Lai et al, 2021). Some studies have documented that parents reported psychological repercussions of a tsunami on their adolescents, including trauma and psychological distress (Hafstad et al, 2012;Hardin et al, 1994;Andrades et al, 2021). Another study found that most children and adolescents demonstrated symptoms of PTSD one year after a big cyclone in Orissa (Udomratn, 2008).…”
Section: Adolescents and Natural Disastersmentioning
confidence: 99%
See 3 more Smart Citations